57Fe Mössbauer and XRD studies on β-FeSi2 prepared by high energy mechanical attrition. (3rd May 2019) - Rajesh, P V; Das, A; Ghosh, B; Das, D
Abstract: The evolution of different phases of Fe–Si binary system on milling elemental Fe and Si powders has been studied by x-ray diffractometry and 57 Fe Mössbauer spectroscopy. The milling has been carried out in argon atmosphere at 1000 rpm using the hardened tungsten carbide medium. The sizes of both Fe and Si are found to be less than 50 nm on milling the mixture for 50 min. Metallic α -FeSi2 formation takes place at this stage due to enhanced reactivity caused by reduction in particle size. The semiconducting β -FeSi2 phase along with ε -FeSi and a metastable Fe–Si solid solution are found to be formed on annealing the milled product at 500 °C. A clean semiconducting β -FeSi2 phase forms on milling Fe and Si for 50 min followed by annealing at 800 °C for 2 h.